1969
DOI: 10.2134/agronj1969.00021962006100030003x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Turfgrasses for Shade Tolerance1

Abstract: Short‐duration growth chamber and field techniques are described for studying shade tolerance of pot‐grown seedling turfgrasses. Performance of eight selections each of bluegrass and red fescue grown at four light intensities from seed to 8 weeks in a growth chamber was evaluated. Varying light intensities were achieved by growing the grasses on shelves in a step‐like design so that the lowest light level was farthest from the illumination source. The four light levels in the growth chamber were measured at 3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0
2

Year Published

1972
1972
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 7 publications
1
8
0
2
Order By: Relevance
“…However, in a greenhouse experiment, Smalley (1981) showed that HD Biljart produced more tillers under decreased PPF after 20 wk of treatment compared with CH ‘Jamestown’, CH ‘Ruby’, ST ‘Pennlawn’, and ST ‘Wintergreen’; to our knowledge, this is the only study showing a HD cultivar exhibiting improved growth compared with CH and ST under reduced irradiance. Overall, HD cultivars were shown to be the poorest performing under foliar shade in previous research (Gardner & Taylor, 2002; Wood, 1969), which agrees with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…However, in a greenhouse experiment, Smalley (1981) showed that HD Biljart produced more tillers under decreased PPF after 20 wk of treatment compared with CH ‘Jamestown’, CH ‘Ruby’, ST ‘Pennlawn’, and ST ‘Wintergreen’; to our knowledge, this is the only study showing a HD cultivar exhibiting improved growth compared with CH and ST under reduced irradiance. Overall, HD cultivars were shown to be the poorest performing under foliar shade in previous research (Gardner & Taylor, 2002; Wood, 1969), which agrees with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…has been accomplished in brush areas of eastern Oklahoma and Missouri after aerial herbicide controJ. 3 The microclimate created by dead standing brush seems well suited to establishment and growth of tall fescue, which has good shade tolerance (9,16). It has been reported that fescue grown under 55% shade has a 5-day-shorter germination time than nonshaded fescue (10).…”
mentioning
confidence: 99%
“…Wood (12) reported significant differences in turf performance for Kentucky bluegrass and red fescue when grown in shade. He contended that the performance of red fescues as a group was superior to that of Kentucky bluegrasses under shade conditions.…”
mentioning
confidence: 99%